1971
DOI: 10.1002/jsfa.2740220212
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and nitrite nitrogen in fresh, stored and processed table beets and spinach from different levels of field nitrogen fertilisation

Abstract: Nitrogen fertilisution increased the content of nitrate-N in fresh table beets arid spinach but had little or no efect on accumulation of nitrite-N. Interconversion of nitrate to nitrite did not occur when fresh beets and spinuch were stored U I 3.5%. Large yiiuntities of nitrate-N were lost by leaching durinR the processinx of canned beets, spinach and piirked .spinach baby food. These processing procedures and stornge of the processed products for six months did not give rise to inereused amounts of nitrite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 14 publications
2
18
1
Order By: Relevance
“…The absence of nitrite-N accumulation in the Swiss chard study is consistent with the response of spinach and table beet nitrate-N concentration to increased N fertiliser (Lee et al 1971). High nitrite-N levels (>6.5 mg/kg), well above the tolerance limit of 1.2 mg/kg proposed for the Chinese National Standard, were detected for several samples in the survey.…”
Section: Discussionsupporting
confidence: 75%
“…The absence of nitrite-N accumulation in the Swiss chard study is consistent with the response of spinach and table beet nitrate-N concentration to increased N fertiliser (Lee et al 1971). High nitrite-N levels (>6.5 mg/kg), well above the tolerance limit of 1.2 mg/kg proposed for the Chinese National Standard, were detected for several samples in the survey.…”
Section: Discussionsupporting
confidence: 75%
“…This is higher than the values reported for canned spinach by Phillips (1968) and Lee et al (1971), who recorded values of 324 and 200 ppm, respectively. As regards the other ions, 3483, 214 arid 1200 ppm were detected for Cl-, SO:-and Ox2-, and K+, respectively, and 1001, 343 and 4100 for Na', NH,' and K', respectively.…”
Section: Canned Spinachcontrasting
confidence: 81%
“…Among the many studies on the influence of nitrogen fertilization upon nitrate levels in vegetables, most have focused on crops that tend to accumulate high levels of nitrate hydrogen. Lee et al (1971) found that increasing the rate of N fertilization of beets and spinach from 0 to 400 lb/A (1 lb/A = 1.12 kg/ha) increased nitrate levels in the crops by 8.8 X and 2.8 X , respectively. Splittstoesser and Vandemark (1974) observed that N fertilization from 20 to 400 lb/A had no effect on nitrate levels in sweet corn, beets and peppers.…”
Section: Soil Type and Fertilitymentioning
confidence: 99%